The Quality of Life and its Relationship to Psychological Burnout of Faculty Members in Saudi Universities - Al-Mulla , Mazen Omer; Musa, Montasir Kamal Al-Din Mohammed (Journal of Ecohumanism, 2024)
The current study aimed to identify the quality of life and its relationship to psychological burnout among faculty members in Saudi universities. The study sample consisted of faculty members in Saudi universities (male and female) in scientific and literary specializations with their various academic degrees in the academic year (2022-2023), whose numbers (202) were chosen randomly. The study used the Quality of Life Scale (1996), prepared by the World Health Organization, based on the psychological burnout of Maslach (1986), and the data was transcribed and statistical processing was performed using the Statistical Package for Social Sciences software. The study reached the following results: The presence of a positive correlation between the quality of life and its relationship to psychological burnout among faculty members in Saudi universities, there was a non-significant decrease in the quality of life among faculty members in Saudi universities. The high level of psychological burnout among faculty members in Saudi universities and the presence of statistically significant differences in the quality of life and its relationship to psychological burnout among faculty members in Saudi universities were attributed to the gender variable in favor of females and the academic rank variable in favor of assistant professors, and the absence of differences in the quality of life among faculty members. In Saudi universities, the variables of academic specialization (scientific, literary), the university and the marital status were not available.